Review of Grant W. Smith's Names as Metaphors in Shakespeare's Comedies - Dorothy Dodge Robbins (Names, 2022)
Names as Metaphors in Shakespeare’s Comedies. By Grant W. Smith. Delaware: Vernon Press. Series in Literary Studies. 2021. Pp. 371. $73.00 (Hardback). ISBN 13: 978-1-64889-018-5. Multiple formats available.